STRATEGI FKPM (FORUM KEMITRAAN POLRI DAN MASYARAKAT) DALAM MENINGKATKAN KESADARAN HUKUM MASYARAKAT (STUDI DI KELURAHAN KADIPIRO KECAMATAN BANJARSARI KOTA SURAKARTA) - Yusnandia Herayu Nurhafida; Moh. Muchtarom; Dewi Gunawati (Asosiasi PPKn, 2020)
The aims of this thesis are to understand about : 1) The reason of FKPM (Forum Kemitraan Polri dan Masyarakat)  establishment in Kadipiro Sub-district; 2) The FKPM?s (Forum Kemitraan Polri dan Masyarakat)  obstacles to improve society legal awareness; 3) FKPM (Forum Kemitraan Polri dan Masyarakat)  implementation strategies to improve society legal awareness.This research uses qualitative research method. This research is descriptive case study research. The data were collected from various resources such as informan, places, events, and documents. This researcher used purposive sampling as its sampling method. In conducting this research, the researcher used interview, observation, and document analysis as its data collecting method. This research used triangulation as its data validation method and observation. This analysis method used interactive analysis model consists of these steps: (1) data collecting; (2) data reduction; (3) data display; (4) conclusion making. Therefore, the research procedure consists of : (1) preparatory step; (2) data collecting step; (3) data analysis step; (4) research report making step. Based on the result of this research, it shows that : 1) Passing through events conducted by FKPM (Forum Kemitraan Polri dan Masyarakat)  can improve its surrounding safety and order and also society legal awareness. 2) In their activities FKPM (Forum Kemitraan Polri dan Masyarakat)  experienced 6 obstacles they are : (1) Limited legal knowledge held by FKPM (Forum Kemitraan Polri dan Masyarakat); (2) The undistributed members of FKPM (Forum Kemitraan Polri dan Masyarakat)  with mediation skill; (3) The activity schedule was not arranged well;   (4) The limited number of supporting facilities for FKPM (Forum Kemitraan Polri dan Masyarakat)  activities; (5) Limited material and non materials support from the government; (6) The society legal awareness is still low.  3) FKPM (Forum Kemitraan Polri dan Masyarakat)  implementation strategies to improve  society legal awareness were conducted through preventive measures such as : (1) FKPM (Forum Kemitraan Polri dan Masyarakat)  integrations to the society; (2) Substitute apparatus for prevention and environmental security; (3) Engaging the society to detect threat for society safety and order early; and through repressive efforts is that becoming mediator when there was a dispute in the society.   Full Paper